Thoracoscopic repair of esophagogastric anastomotic fistula using a pedicled pleural flap: a case report and literature review - Li, Yujian; Deng, Yongjun; Zou, Jianbin (Frontiers in Oncology, 2026)
BackgroundEsophagogastric anastomotic leakage is one of the most serious complications following radical esophagectomy for esophageal cancer. Anastomotic leakage leads to prolonged hospitalization, increased medical costs, reduced quality of life, and higher mortality. Thus, early detection and effective treatment of this complication are crucial. Successful treatment of anastomotic fistula hinges on closing the fistula tract.Case SummaryWe treated a patient with locally advanced mid-thoracic esophageal squamous cell carcinoma. After two cycles of neoadjuvant chemotherapy, he underwent minimally invasive thoracoscopic esophagectomy using the McKeown procedure. However, on postoperative day 11, he developed a left cervical esophagogastric anastomotic leakage that extended into the right thoracic cavity, leading to empyema formation. After controlling the acute infection, we innovatively used a parietal pleural pedicled flap, assisted by video-assisted thoracoscopy, to repair the anastomotic fistula. Additionally, we performed thoracoscopic fiberboard decortication for the empyema. Subsequent measures included continuous low-pressure negative pleural suction in the right thoracic cavity to promote pulmonary re-expansion and eliminate residual cavity, as well as continuous irrigation and drainage to maintain a clean postoperative environment in the right thoracic cavity. These comprehensive treatments led to complete healing of the esophagogastric anastomotic fistula, and the patient had an uneventful recovery without any sequelae.ConclusionThis case demonstrates that pedicled pleural flaps are a viable and practical option for repairing anastomotic fistulas. Our treatment approach offers advantages of simplicity, practicality, and minimal invasiveness, providing a reference for managing esophagogastric anastomotic fistula patients.